The Influence of RTK GNSS Antenna Heights on Multipath Error - Isnan, Sarah; Hardy, A.; Hisan, Wan Baderul; Amir, Mohamad Abu Ubaidah; Razali, Mohd Norsyarizad; Azzeri, M.N; Ahmad, Mohd Arif; R, Zulkifly M.; Rosly, Afiqah; Rahman, Ainul; Aziz, Adenen; Muhamad, Siti Nur (International Journal of Engineering and Technology, 2018)
Hydrographic surveying is critical to provide safe navigation and route selection to the vessels. Since GNSS has evolved throughout the decade, it became a fundamental equipment for survey. Real Time Kinematic (RTK) GNSS is one of the GNSS technology, which capable in computing position in real time and produce centimetre accuracy. However, this GNSS equipment is susceptible to multipath error causing error in positioning computation. This project attempts to investigate how different antenna heights will effect the positioning accuracy and size of multipath error on RTK GNSS. Various types of analysis have been done in order to determine whether different antenna heights will affect the positional accuracy and size of multipath error. The result shows that different antenna heights effect the positional accuracy and size of the multipath error and this will provide basic guides in order to carry out hydrographic survey. Conclusion and future research also has been made in order to guide researchers in conducting future projects.